Simulation of a multiple heat source supercritical ORC (Organic Rankine Cycle) for vehicle waste heat recovery. (15th December 2015) - Glover, Stephen; Douglas, Roy; De Rosa, Mattia; Zhang, Xiaolei; Glover, Laura
Abstract: This paper presents the analysis and results of a supercritical WHR (Waste Heat Recovery) ORC (Organic Rankine Cycle) modelling study. The study focuses on multiple series heat sources from vehicles and the potential of WHR ORC's to convert this into useful work. The work presented is generally applicable to any waste heat recovery system, either stationary or mobile and, with careful consideration, is also applicable to single heat sources. The simulation model simultaneously calculates WHR ORC performance for multiple circuit layouts related to the position of the regenerator. The work presented details the optimisation of WHR ORC performance with regard to fluid selection from a distinct pool of preselected fluids and from an operational parameter perspective at realistic drive cycle related heat boundary conditions. The paper also looks at WHR ORC performance with regard to condenser pressure and atmospheric conditions for different fluids. The paper concludes with estimated WHR ORC vehicle fuel consumption improvement figures. Highlights: Three heat sources modelled, two supplying the energy in a fixed heat ratio. Maximising circuit efficiency can be less important than maximising heat input. Balancing the circuit is critical at low heat ratios to maximise performance. Critical circuit performance link between fluid critical and coolant temperatures. WHR has the potential to significantly improve vehicle fuel economy.